Pozycja obywatela konsumenta wobec przedsiębiorstwa w Polsce. Aspekty prawne i ich implikacje społeczne: [Position of a citizen-consumer in relation to enterprises in Poland] (Studia Prawnicze / The Legal Studies, 1984)
The article consists of four parts. In the first part the author enumerates main topics of the work. The 'intention of the author is to examine and define the character and sources of dependence between the citizen and enterprise which organizes and distributes services. Having decided of juridical research, the author, however, tries to observe actual behaviour of an enterprise rendering services for the customer in the course of organizing and rendering them.In the second part of the article the author points to the diminishing role of a civil law contract in relations between the enterprise and citizen and, at the same time, expanding domination of the enterprise over its contracting party. The contract does not play its functional and organizational role any more. The enterprise considers it a formal act of distribution of given service (good) not much differing from other legal instruments (e f. administrative act). Excessive monopolization of the Polish economy, persisting monopolistic trends, the phenomenon of the so-called imperativization of civil law relation between the enterprise and citizen as well as legislative activities of the enterprise (the so-called legislation proper or the so-called quasi-legislation) are the main sources of domination of the enterprise.The third, detailed part, of the article, presents, on the basis of selected e:eamples, the scone, instruments and methods of domination of the enterprise over the citizen. Final remarks consist of general conclusions. If the legislator were more interested in creating general terms in the field of some types of services it would considerably limit spontaneous phenomena, because many enterprises not only ex lege but also as a results of usurpation try to concentrate functions in relation to contracting patty (legislative, judicial, executory, administrative and others) which cannot be included into the traditional construction of a civil law contract.